(untitled) (Journal of Nobel Medical College, 2022)
Background: Benzodiazepines are regularly prescribed to treat patients in alcoholic withdrawal. After analyzing pharmacology of benzodiazepines, diazepam is faster metabolized and concentrated in the liver, as an active metabolite whereas lorazepam is metabolized in liver by conjugation and excreted in urine. lorazepam being a drug of choice used in patients with deranged liver functions is needed to be compared with that of diazepam. The objective of the study is the comparasion of two benzodiazepines in treatment of alcohol dependence syndrome in Nepal. Material and Methods: This was a prospective, open label study carried out in Department of Psychiatry, Nobel Medical College and Teaching Hospital, Biratnagar. 50 patients (25 in each) aged between 25 to 65 years diagnosed as alcohol dependent admitted and grouped in either diazepam or lorazepam alternatively. The doses prescribed to the diazepam group and lorazepam group are 30 mg/day and 8 mg/day respectively in divided doses. For both the treatment groups, the dose was tapered every alternate day for 10 days. The Clinical Institute Withdrawal Assessment Alcohol Scale Revised (CIWA-Ar) scale was used for withdrawal symptoms scoring on the baseline and day 10. Lab Investigations were performed but were not a part of the study. Results: Out of the Fifty patients included in the study, at day 0, the mean CIWA-Ar scores were similar in both the treatment groups: 24.38±5.03 in the diazepam group and 24.79±6.42 in the lorazepam group. There was a significant intragroup decrease in the CIWA-Ar scores measured from Day 0 to the end of 10 days (p<0.0001) in both treatment groups; there was no significant difference between the two groups Conclusion: Diazepam and lorazepam are equally effective in alcohol withdrawal detoxification.